Reclaimed clay sand and method for producing a lost foam reinforcement layer coating using the same

CN122895460APending Publication Date: 2026-10-13WUHAN FENGHUAN XINCHENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610839710.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]但是,一般的,这些废弃黏土砂,混有黏土,少量煤粉,其中烧结的死黏土占废砂总比约0.5-1%,活性黏土比例较高,传统处理方法就是铸造企业免费或者补贴方式,送到水泥厂消化,客观上增加了铸造企业成本,现在由于水泥企业产能过剩,基本上拒收该废砂,于是该废砂就成为一般固废,铸造界研究水玻璃砂再生工程技术人员,专家学者,企业都耗费很大精力,采取水洗等方式试图处理能够再次应用,但是要么成本解决新砂成本,要么砂型性能达不到要求,也有球磨后高温300-500度干烧等工艺,但是工艺成本高不适用于大型作业场景

Benefits of technology

本发明采用低强度干法球磨工艺替代传统水洗和高温煅烧,整个再生及涂料制备过程无废水、废气、废渣产生,完全符合绿色制造和固废减量化要求,从根本上解决了铸造企业废弃黏土砂处置难题;再生砂制备成本仅为新石英砂的30%以下,每吨消失模加固层涂料成本可节约相当于新石英砂的采购成本;同时利用再生砂中保留的活性黏土成分,可减少商品化消失模粘结剂用量10-20%,进一步降低涂料综合成本50%以上;采用低磨球量、短时间球磨工艺,仅选择性去除石英砂表面部分烧结死黏土,保留大部分活性黏土,工艺流程短、设备投资少、能耗低,适合工业化大规模连续生产;再生砂保留了原砂良好的粒型,制备的涂料流平性好、滴淌时间短,可均匀覆盖泡沫模型表面的沟槽和孔洞;烘干后涂料强度高、韧性好,指甲划痕无掉粉剥落,泡沫侧面挤压无成片剥落,完全满足消失模铸造第二层至第四层加固层的使用要求,且不影响铸件表面质量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to solid waste regeneration and application technical field, concretely is the method for preparing the lost foam reinforcing layer coating of regenerated clay sand and the clay sand, including quartz sand particle and 50-100 mesh mullite particle mixture; The mass ratio of mullite particle in the mixture is 25-35%, the particle size of the mixture is 30-100 mesh; The mass ratio of effective clay in the mixture is: 2-5%; The mass ratio of free carbon is: 0.5-1%; The mass ratio of silicon oxide is: 92-95%; The quartz sand particle and mullite particle surface are all covered with clay layer.The present application adopts low-strength dry ball milling process to replace traditional water washing and high-temperature calcination, the whole regeneration and coating preparation process does not produce waste water, waste gas and waste residue, completely meets the requirements of green manufacturing and solid waste reduction, fundamentally solves the disposal problem of waste clay sand of foundry enterprises.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste recycling and application technology, specifically to recycled clay sand and a method for using the clay sand to prepare a lost foam reinforcement coating. Background Technology

[0002] Traditional cast steel often uses water glass, with resin used as a binder and quartz sand as the refractory aggregate. Water glass sand includes ordinary and modified types, and the resins are mostly furan resin and alkali-phenolic resin. Water glass has relatively low regeneration efficiency, and the waste is highly alkaline, making it a hazardous waste and resulting in high disposal costs for companies. Furan resin sand has a high regeneration rate, but it is also expensive, and the curing agent is toxic, while the resin combustion produces significant amounts of waste gas. Alkali-phenolic resin regeneration is also troublesome and has a low regeneration rate.

[0003] Clay sand, as an inorganic binder, produces no waste gas emissions and is inexpensive. However, the strength of the sand mold is difficult to meet the requirements of cast steel. It is widely used in cast iron, but not often directly used in cast steel. At the end of the last century, some foundry companies used clay sand as the outer mold for molding, and the sand core was bonded with resin. This resulted in a high regeneration rate of clay sand and low overall cost. The waste sand was mainly clay sand, mixed with a small amount of resin core sand.

[0004] However, these waste clay sands are generally mixed with clay and a small amount of coal powder. Sintered dead clay accounts for about 0.5-1% of the total waste sand, while the proportion of active clay is relatively high. The traditional treatment method is for foundry companies to send them to cement plants for disposal free of charge or with subsidies. This objectively increases the cost for foundry companies. Now, due to the overcapacity of cement companies, they basically refuse to accept this waste sand. As a result, this waste sand becomes general solid waste. Foundry engineers, experts, scholars, and companies have spent a lot of effort researching water glass sand recycling engineering, trying to treat it for reuse through methods such as water washing. However, either the cost of new sand is offset by the cost, or the sand mold performance does not meet the requirements. There are also processes such as ball milling followed by high-temperature dry burning at 300-500 degrees Celsius, but the process cost is high and not suitable for large-scale operation scenarios.

[0005] Based on this, the present invention provides recycled clay sand and a method for preparing lost foam reinforcement coatings using the clay sand, in order to solve the above-mentioned technical problems. Summary of the Invention

[0006] The purpose of this invention is to provide recycled clay sand and a method for using the clay sand to prepare a lost foam reinforcement coating, thereby solving the problems mentioned in the background art.

[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention proposes a recycled clay sand for steel casting, comprising a mixture of quartz sand particles and 50-100 mesh mullite particles; The mass percentage of mullite particles in the mixture is 25-35%, and the particle size of the mixture is 30-100 mesh. The mass percentage of effective clay in the mixture is 2-5%; The mass percentage of the free carbon is 0.5-1%; The mass percentage of silicon dioxide is 92-95%. Both the quartz sand particles and the mullite particles are coated with a clay layer.

[0008] Preferably, the quartz sand particles are waste clay quartz sand particles generated from the steel casting process. The original sand of the waste clay quartz sand particles is sea sand or aeolian sand. The mass percentage of silica in the original sand is greater than 97%. The particle size of the original sand is 30-70 mesh. The total mass percentage of clay in the waste clay quartz sand is 4-8%, the mass percentage of dead clay is 1-2%, the mass percentage of coal powder is 1-3%, and the mass percentage of free carbon is 0.5-1%.

[0009] Based on recycled clay sand, this invention also proposes a method for regenerating recycled clay sand for steel casting, comprising the following steps: A1. Add the waste clay quartz sand produced in the steel casting process and 50-100 mesh mullite to the ball mill at a mass ratio of 3-4:1. The number of grinding balls in the ball mill is 1 / 4-1 / 5 of the number of grinding balls in normal operation. The ball milling time is 20-30 minutes. A2. The material after ball milling is subjected to dust removal, iron removal and screening in sequence to obtain 30-100 mesh recycled clay sand.

[0010] Preferably, the ball mill used in step S1 is an intermittent ball mill.

[0011] Preferably, the ball mill used in step S1 is a continuous ball mill, and the tail discharge port of the continuous ball mill is equipped with a 100-mesh screen. The material discharge speed is controlled by adjusting the lifting bolt to change the inclination of the continuous ball mill.

[0012] Based on recycled clay sand and its recycling method, this invention also proposes a method for manufacturing a lost foam reinforcement coating using recycled clay sand, comprising the following steps: B1. Place the recycled clay sand for casting steel prepared in steps A1 to A2 and the lost foam binder in a mixing device at a preset mass ratio, and dry mix for 30-120 minutes to obtain a dry mixture. B2. Add deionized water to the dry mixture, controlling the mass ratio of the mixture to the deionized water to be 10:5-7. Stir at a speed of 150-200 rpm for more than 120 minutes. After stirring, let it stand for 10-30 minutes, test and adjust the Baume degree of the mixture to 68-74 to obtain the lost foam reinforcement coating.

[0013] Preferably, the lost foam bonding agent is Guilin No. 5 bonding agent, and the mass ratio of recycled clay sand for steel casting to Guilin No. 5 bonding agent is 10-12:1.

[0014] Preferably, in step S1, 20-30 parts by weight of high-alumina bauxite with a particle size of 70-150 mesh and 0.5-1 parts by weight of waste carbon fiber with a length of 1-3 mm are added to recycled clay sand for steel casting to obtain mixed aggregate, wherein the mass ratio of the mixed aggregate to the lost foam binder is 9:1.

[0015] Based on the method for manufacturing lost foam reinforcement coatings using recycled clay sand, this invention also proposes a lost foam reinforcement coating, which is prepared by the method for manufacturing lost foam reinforcement coatings using recycled clay sand.

[0016] Preferably, after the coating is applied to the surface of the foam model, it is placed in an oven to dry for more than 2 hours until constant weight. After drying, the coating shows no powdering or peeling after being tested by a fingernail scratch test, and no large-scale peeling after being tested by the extrusion test on the side and vertical surface of the foam. The coating is used as the second to fourth reinforcing layers in lost foam casting.

[0017] Compared with the prior art, the beneficial effects of the present invention are: This invention uses a low-intensity dry ball milling process to replace traditional water washing and high-temperature calcination. The entire recycling and coating preparation process generates no wastewater, waste gas, or waste residue, fully meeting the requirements of green manufacturing and solid waste reduction. It fundamentally solves the problem of waste clay sand disposal in foundry enterprises. The cost of recycled sand preparation is only less than 30% of that of new quartz sand, and the cost of each ton of lost foam reinforcement coating can be reduced by the equivalent of the purchase cost of new quartz sand. At the same time, by utilizing the active clay components retained in the recycled sand, the amount of commercial lost foam binder can be reduced by 10-20%, further reducing the overall cost of coatings by more than 50%. Employing a low-ball-volume, short-time ball milling process, only the sintered dead clay on the surface of the quartz sand is selectively removed, while retaining most of the active clay. This process is short, requires less equipment investment, and has low energy consumption, making it suitable for large-scale continuous industrial production. The recycled sand retains the good particle shape of the original sand, resulting in coatings with good leveling properties and short dripping time, which can evenly cover the grooves and pores on the surface of the foam model. After drying, the coating has high strength and good toughness, with no powdering or peeling when scratched by a fingernail, and no large-scale peeling when the foam sides are squeezed. It fully meets the requirements for the second to fourth reinforcing layers in lost foam casting and does not affect the surface quality of the casting. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0019] I. Materials: Unless otherwise specified, all materials used in this invention are commercially available, including: Waste clay quartz sand: Waste sand for cast steel outer molds. The original sand is Bohai Sea sand, with SiO2≥97%, original sand particle size 30-70 mesh, total clay content 6.2%, dead clay 1.5%, coal powder 2.1%, free carbon 0.8%, and SiO2≥93% after iron removal. It was purchased from a steel casting company in Ezhou, Hubei Province. Mullite: 50-100 mesh, Al2O3≥72%, Fe2O3≤0.5%, purchased from a refractory materials company in Zhengzhou, Henan Province; High-alumina bauxite: 70-150 mesh, Al2O3≥88%, Fe2O3≤1.0%, purchased from a refractory materials company in Yangquan, Shanxi Province; Waste carbon fiber: 1-3mm in length and 7μm in diameter, from carbon fiber prepreg scraps, purchased from a composite materials company in Changzhou, Jiangsu. Guilin No. 5 Adhesive: Powdered adhesive for lost foam casting coatings, solid content ≥95%, manufactured by a foundry materials company in Guilin, Guangxi. Deionized water: conductivity ≤10μS / cm, pH=6.5-7.5, prepared in the laboratory; Based on this, the effects of different ball milling parameters on the particle size distribution of regenerated sand were studied. To optimize the regeneration process parameters of this invention, the effects of ball milling time, number of milling balls, and mullite ratio on the particle size distribution of regenerated sand were investigated. The experimental results are as follows: Test for particle size distribution of recycled sand: The test shall be conducted in accordance with GB / T 2684-2009 "Test Methods for Foundry Sand and Mixtures", using the standard test sieve method. Weigh 100.0g of recycled sand sample dried to constant weight, place it on top of the standard test sieve, and vibrate it on a vibrating sand screening machine for 15 minutes. Weigh the residue on each sieve size and calculate the cumulative residue percentage for each sieve size.

[0020] Test for effective clay content in recycled sand: Perform the methylene blue adsorption method according to GB / T 2684-2009.

[0021] Coating performance testing includes Baumé degree, leveling properties, dripping time, drying strength, toughness, and casting surface quality testing. The effect of ball milling time on the particle size distribution of regenerated sand: Fixed conditions: the mass ratio of waste clay-quartz sand to mullite was 3.5:1 (mullite accounted for 22.2%), the number of grinding balls was 20% (1 / 5) of the normal amount, and the grinding time was changed to 15, 20, 25, 30 and 40 minutes respectively. The particle size distribution of the recycled sand is shown in Table 1.

[0022] Table 1. Particle size distribution of regenerated sand under different ball milling times (cumulative sieve residue, %)

[0023] As shown in Table 1, when the ball milling time is too short (15 minutes), the dead clay on the surface of the quartz sand is not sufficiently removed, and the content of coarse particles (>30 mesh) is high, affecting the leveling properties of the coating. When the ball milling time is 20-30 minutes, the particle size distribution of the recycled sand is uniform, and the proportion of 30-100 mesh particles reaches more than 90%, which meets the particle size requirements of lost foam coating aggregate. When the ball milling time exceeds 30 minutes (40 minutes), the quartz sand particles are excessively crushed, and the content of fine powder (<140 mesh) increases significantly, which leads to increased coating viscosity, decreased air permeability, and easy formation of porosity defects in the casting. Therefore, the present invention selects a ball milling time of 20-30 minutes.

[0024] The effect of grinding ball number on the particle size distribution of regenerated sand: Fixed conditions: waste clay-quartz sand to mullite mass ratio 3.5:1, ball milling time 25 minutes, the number of grinding balls was changed to 10%, 20% (1 / 5), 25% (1 / 4), and 50% (1 / 2) of the normal amount, and the particle size distribution of the recycled sand is shown in Table 2.

[0025] Table 2. Particle size distribution of regenerated sand under different numbers of grinding balls (cumulative sieve residue, %)

[0026] Table 2 shows that when the number of grinding balls is too small (10%), the grinding intensity is insufficient, the content of coarse particles is high, and the removal of dead clay is inadequate. When the number of grinding balls is 20-25%, the particle size distribution of the regenerated sand is optimal, with 30-100 mesh particles accounting for more than 91%. When the number of grinding balls is too large (50%), the grinding intensity is too high, the quartz sand particles are severely broken, the content of fine powder increases significantly, and the coating performance deteriorates. Therefore, this invention selects a grinding ball number of 1 / 4 to 1 / 5 of the normal operating grinding ball number.

[0027] The effect of mullite ratio on the particle size distribution of recycled sand: Fixed conditions: ball milling time 25 minutes, number of grinding balls 20% of normal, mullite mass ratio changed to 20%, 25%, 30%, 35%, 40% respectively, and the particle size distribution of recycled sand is shown in Table 3.

[0028] Table 3. Particle size distribution of recycled sand with different mullite ratios (cumulative sieve residue, %)

[0029] As shown in Table 3, when the mullite content is below 25%, the grinding media is insufficient, dead clay is not adequately removed, and the content of coarse particles is high. When the mullite content is between 25% and 35%, the particle size distribution of the recycled sand is uniform, and the proportion of 30-100 mesh particles remains stable at around 92%. When the mullite content exceeds 35%, although the particle size distribution does not change significantly, it increases the cost of raw materials and reduces the proportion of quartz sand in the recycled sand, affecting the refractory performance of the coating. Therefore, this invention selects a mullite mass ratio of 25-35%.

[0030] II. Process: Example 1: Based on the materials and fixing conditions, this example prepares a coating for reinforcing the lost foam casting layer of cast iron. The specific steps are as follows: Raw material pretreatment and metering: Take 150 kg of waste clay quartz sand, manually sort it to remove large impurities, and dry it in a 105℃ electric heating blast drying oven for 2 hours until constant weight; take 50 kg of 50-100 mesh mullite; accurately weigh 18.18 kg of Guilin No. 5 binder; prepare 109.1 kg of deionized water.

[0031] Preparation of recycled clay sand: 150 kg of waste clay quartz sand and 50 kg of mullite were added to a Φ400×600 mm intermittent ball mill, and grinding balls of 20% of the normal working mass were added. The milling was carried out for 25 minutes. After ball milling, the material was successively subjected to dust removal by a pulse bag filter, iron removal by a magnetic separator, and screening by a vibrating screen to obtain 30-100 mesh recycled clay sand. Its effective clay content was 3.2%, free carbon was 0.7%, and SiO2 content was 93.5%.

[0032] Preparation of lost foam reinforcement coating: Add 200 kg of recycled clay sand and 18.18 kg of Guilin No. 5 binder to a double cone mixer and dry mix for 60 minutes; transfer to a low-speed mixer, add 109.1 kg of deionized water, and stir at 180 r / min for 150 minutes; let stand for 20 minutes, and test the Baume degree to be 71°Be' to obtain the finished coating.

[0033] Application test: The coating was applied to the surface of the EPS foam model of HT200 cast iron parts and dried at 50℃ for 2.5 hours to constant weight. The coating was repeated 3 times (from the second to the fourth layer). After casting, the surface of the casting was smooth and free of defects such as sand adhesion, air holes, and cracks. The surface roughness Ra=12.5μm.

[0034] Example 2: This example describes the preparation of a coating for reinforcing a lost foam casting layer on cast steel. The specific steps are as follows: Raw material pretreatment and metering: Take 175 kg of waste clay quartz sand and pretreatment as in Example 1; take 70 kg of 50-100 mesh mullite; take 61.25 kg of 70-150 mesh high alumina bauxite; take 1.96 kg of waste carbon fiber; accurately weigh 30.91 kg of Guilin No. 5 binder; prepare 200.9 kg of deionized water.

[0035] Preparation of recycled clay sand: 175 kg of waste clay quartz sand and 70 kg of mullite were continuously fed into a Φ600×4000 mm continuous ball mill through a quantitative feeder at a feeding speed of 500 kg / h; the number of grinding balls was 25% of the normal amount; the inclination of the ball mill was adjusted to 3°; and the material residence time was about 28 minutes. After ball milling, the material was subjected to dust removal, iron removal, and screening to obtain 30-100 mesh recycled clay sand. Its effective clay content was 2.8%, free carbon was 0.6%, and SiO2 content was 94.2%.

[0036] Preparation of lost foam reinforcement coating: 245 kg of recycled clay sand, 61.25 kg of high-alumina bauxite and 1.96 kg of waste carbon fiber were premixed for 30 minutes; 30.91 kg of Guilin No. 5 binder was added and dry-mixed for 90 minutes; 200.9 kg of deionized water was added and stirred at 170 r / min for 180 minutes; after standing for 25 minutes, the Baume degree was tested and found to be 73°Be', and the finished coating was obtained.

[0037] Application test: The coating was applied to the surface of the EPS foam model of ZG230-450 cast steel parts and dried at 60℃ for 3 hours to constant weight. The coating was repeated 3 times. After casting, the surface quality of the casting was good, with no defects such as sand adhesion or cracks, and the surface roughness Ra=12.5μm.

[0038] To verify the superiority of the technical solution of the present invention, the following comparative examples were set up. Except for the parameters specifically mentioned, the raw materials, processes and test conditions were the same as those in Example 1: Comparative Example 1: Mullite content 20%.

[0039] Comparative Example 2: Ball milling time 40 minutes.

[0040] Comparative Example 3: The number of grinding balls is 50% of the normal amount.

[0041] Comparative Example 4: Traditional water washing regeneration method, which involves washing five times and then drying and sieving.

[0042] III. Performance Testing: All performance tests of this invention were conducted in a standard laboratory environment of 25℃±1℃ and 50%±5% relative humidity. All samples were prepared and tested under the same conditions. Each test was repeated 3 times, and the arithmetic mean was taken as the final result.

[0043] a. Recycled sand particle size distribution test: The test shall be conducted in accordance with GB / T2684-2009 "Test Methods for Foundry Sand and Mixtures", using the standard test sieve method. Weigh 100.0g ± 0.1g of recycled sand sample dried to constant weight (drying at 105℃ ± 2℃ for 2 hours), place it on top of stacked standard test sieves (from top to bottom: 30 mesh, 50 mesh, 70 mesh, 100 mesh, 140 mesh, 200 mesh, base plate), and install it on an SZS-Ⅲ type vibrating sand screening machine and vibrate for 15 minutes; weigh the amount of residue on each sieve number, accurate to 0.1g, and calculate the cumulative percentage of residue on each sieve number and the total proportion of particles between 30 and 100 mesh.

[0044] b. Determination of effective clay content in recycled sand: Perform the methylene blue adsorption method as per GB / T2684-2009. Weigh 5.000 g ± 0.001 g of the dried recycled sand sample to constant weight, place it in a 250 mL Erlenmeyer flask, add 50 mL of distilled water, and stir on a magnetic stirrer at 300 r / min for 5 minutes to completely disperse the sample; add 10 mL of 0.2% methylene blue solution and continue stirring for 1 minute; use a glass rod to dip a drop of the solution onto medium-speed qualitative filter paper and observe whether a clear blue halo appears in the center of the spot; if not, continue adding 1 mL of methylene blue solution, stir for 1 minute, and test again until a clear blue halo appears and remains for 5 minutes; record the total volume of methylene blue consumed, V (mL), and calculate the effective clay content using the following formula: Effective clay content (%) = (V × 0.014) / 5 × 100; In the formula: 0.014 is the number of grams of clay equivalent to one milliliter of 0.2% methylene blue solution.

[0045] c. Energy consumption detection for recycled sand preparation: The total power consumption of the ball mill, dust collector, magnetic separator and vibrating screen in the recycled sand preparation process is measured by a DT862-4 power monitoring instrument. The energy consumption per unit mass of recycled sand is obtained by dividing the total power consumption by the total mass of recycled sand prepared, and the unit is kWh / t.

[0046] d. Baumé degree test of coating: Pour the well-stirred coating into a 250mL clean graduated cylinder, and gently place the clean and dry Baumé meter into the center of the coating, avoiding contact with the cylinder wall and bottom; after the Baumé meter stabilizes, read the value at the point where the liquid level is tangent to the Baumé meter scale, accurate to 0.1°Be'.

[0047] e. Coating leveling property test: Place a clean 100mm×100mm glass plate horizontally on the test table, use a pipette to draw 0.5mL of well-stirred coating, and drop it vertically onto the center of the glass plate; after standing for 30 seconds, observe the shape and uniformity of the leveled coating, and judge according to the following standards: Good: The coating is a regular circle with smooth edges, uniform thickness, and no accumulation or dripping. General: The coating is irregularly circular, with slight local accumulation and no obvious sagging; Poor: The coating shape is irregular, with obvious brush marks or runs.

[0048] f. Paint dripping time test: Place a 1mm thick standard scraper on a 100mm×200mm clean glass plate, and use a scraper to evenly spread the paint on the glass plate to form a uniform coating; quickly remove the scraper and place the glass plate vertically, and start the stopwatch at the same time; record the time from vertical placement to when the paint stops dripping, accurate to 1 second.

[0049] g. Coating drying strength test (fingernail scratch method): A 100mm × 100mm × 20mm EPS foam board (density 20kg / m³) is tested. 3 The surface is coated with a 1mm thick paint and dried in an electric heating drying oven at 50℃±2℃ until constant weight (the difference in weight between two consecutive weighings ≤0.1g); three parallel scratches, each approximately 2cm long and 1cm apart, are made on the coating with a fingernail at a 45° angle using a force of approximately 5N; the results are judged according to the following standards: Acceptable: No powdering or peeling at the scratched area; Unacceptable: Slight powder shedding at the scratched areas; Seriously unqualified: There is obvious powdering or peeling at the scratched area.

[0050] h. Coating toughness test (foam side extrusion method): A 100mm × 100mm × 50mm EPS foam block (density 20kg / m³) is used for testing. 3 Apply a 1mm thick layer of paint to the side facade and dry it in an electric heating drying oven at 50℃±2℃ until constant weight. Press the center area of ​​the coating vertically with your thumb using a force of approximately 10N, pressing to a depth of approximately 5mm. Judge according to the following standards: Pass: The coating is free from cracks and peeling. Unacceptable: Localized cracking of the coating without peeling. Seriously unqualified: The coating shows signs of peeling off in large patches.

[0051] i. Surface roughness inspection of castings: After casting and cooling, the molding sand on the surface of the castings is cleaned. A TR200 surface roughness tester is used to randomly select 5 different locations on the surface of the castings for inspection. The arithmetic mean is taken as the final result, and the unit is μm.

[0052] j. Surface defect detection of castings: The entire surface of the casting is inspected by visual observation. Defects such as sand adhesion, porosity, cracks, and slag inclusions are recorded and classified according to their severity.

[0053] Table 4 shows a comparison of the overall performance of the examples and comparative examples.

[0054] Table 4. Comparison of overall performance between the embodiments and comparative examples.

[0055] IV. Analysis Conclusion: As can be seen from Tables 1-4: This invention optimizes the ball milling time, the number of milling balls, and the mullite ratio to control the proportion of 30-100 mesh particles in recycled sand to over 92%, and stabilizes the effective clay content in the optimal range of 2-5%. This ensures both the leveling and breathability of the coating, while fully utilizing the binding effect of the active clay and reducing the amount of commercial binders used.

[0056] Comparative Examples 1-3 deviated from the parameter range of the present invention, resulting in poor particle size distribution of recycled sand or abnormal effective clay content, which ultimately led to a decline in coating performance and various defects in castings, fully verifying the scientificity and rationality of the parameter range of the present invention.

[0057] Compared with the traditional water washing and regeneration method in Comparative Example 4, the energy consumption for regenerated sand preparation in this invention is reduced by more than 85%, the overall cost of coatings is reduced by more than 50%, and no wastewater is generated, resulting in significant environmental and economic benefits.

[0058] The coatings prepared in Examples 1 and 2 of this invention meet the requirements for use as a reinforcing layer in lost foam casting. Example 1 is suitable for small-batch, multi-variety production, while Example 2 is suitable for large-scale industrial production and can meet the higher requirements of cast steel parts.

[0059] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0060] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A type of recycled clay sand for cast steel, characterized in that, Including a mixture of quartz sand particles and 50-100 mesh mullite particles; The mass percentage of mullite particles in the mixture is 25-35%, and the particle size of the mixture is 30-100 mesh. The mass percentage of effective clay in the mixture is 2-5%; The mass percentage of the free carbon is 0.5-1%; The mass percentage of silicon dioxide is 92-95%. Both the quartz sand particles and the mullite particles are coated with a clay layer.

2. The recycled clay sand for cast steel according to claim 1, characterized in that, The quartz sand particles are waste clay quartz sand particles generated from the steel casting process. The original sand of the waste clay quartz sand particles is sea sand or aeolian sand. The mass percentage of silica in the original sand is greater than 97%. The particle size of the original sand is 30-70 mesh. The total mass percentage of clay in the waste clay quartz sand is 4-8%, the mass percentage of dead clay is 1-2%, the mass percentage of coal powder is 1-3%, and the mass percentage of free carbon is 0.5-1%.

3. A method for regenerating recycled clay sand for cast steel, characterized in that, Includes the following steps: A1. Add the waste clay quartz sand produced in the steel casting process and 50-100 mesh mullite to the ball mill at a mass ratio of 3-4:

1. The number of grinding balls in the ball mill is 1 / 4-1 / 5 of the number of grinding balls in normal operation. The ball milling time is 20-30 minutes. A2. The material after ball milling is subjected to dust removal, iron removal and screening in sequence to obtain 30-100 mesh recycled clay sand.

4. The method for regenerating recycled clay sand for cast steel according to claim 3, characterized in that, The ball mill used in step S1 is an intermittent ball mill.

5. The method for regenerating recycled clay sand for cast steel according to claim 3, characterized in that, The ball mill used in step S1 is a continuous ball mill. The tail discharge port of the continuous ball mill is equipped with a 100-mesh screen. The inclination of the continuous ball mill is changed by adjusting the lifting bolts to control the material discharge speed.

6. A method for manufacturing a lost foam reinforcement layer coating using recycled clay sand, characterized in that, Includes the following steps: B1. Place the recycled clay sand for casting steel prepared in steps A1 to A2 and the lost foam binder in a mixing device at a preset mass ratio, and dry mix for 30-120 minutes to obtain a dry mixture. B2. Add deionized water to the dry mixture, controlling the mass ratio of the mixture to the deionized water to be 10:5-7. Stir at a speed of 150-200 rpm for more than 120 minutes. After stirring, let it stand for 10-30 minutes, test and adjust the Baume degree of the mixture to 68-74 to obtain the lost foam reinforcement coating.

7. The method for manufacturing a lost foam reinforcement layer coating using recycled clay sand according to claim 6, characterized in that, The lost foam bonding agent is Guilin No. 5 bonding agent, and the mass ratio of recycled clay sand for steel casting to Guilin No. 5 bonding agent is 10-12:

1.

8. The method for manufacturing a lost foam reinforcement layer coating using recycled clay sand according to claim 6, characterized in that, In step S1, 20-30 parts by weight of high-alumina bauxite with a particle size of 70-150 mesh and 0.5-1 parts by weight of waste carbon fiber with a length of 1-3 mm are added to recycled clay sand for steel casting to obtain mixed aggregate. The mass ratio of the mixed aggregate to the lost foam binder is 9:

1.

9. A coating for reinforcing lost foam casting, characterized in that, It is prepared by the method of manufacturing lost foam reinforcing layer coating from recycled clay sand according to any one of claims 6 to 8.

10. The lost foam reinforcement coating according to claim 9, characterized in that, After the coating is applied to the surface of the foam model, it is placed in an oven to dry for more than 2 hours until constant weight. The dried coating shows no powdering or peeling after being tested by a fingernail scratch test, and no large-scale peeling after being tested by extrusion on the side and vertical surfaces of the foam. The coating is used as the second to fourth reinforcing layers in lost foam casting.